2019
DOI: 10.1096/fj.201900338r
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1α interacts with a novel ciliary targeting sequence of polycystin‐1 and regulates polycystin‐1 trafficking

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic disorder causing renal failure. Mutations of polycystic kidney disease 1 (PKD1) account for most ADPKD cases. Defective ciliary localization of polycystin‐1 (PC1), a large integral membrane protein encoded by PKD1, underlies the pathogenesis of a subgroup of patients with ADPKD. However, the mechanisms by which PC1 and other ciliary proteins traffic to the primary cilium remain poorly understood. A ciliary targeting sequence (CTS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
(98 reference statements)
1
12
0
Order By: Relevance
“… 48 , 49 During the transport of glucose into cells, glycogen synthesis, oxidative decomposition and other metabolic processes, protein phosphatase 1 (PP1) pathway is the most important metabolic process for synthesizing glucose into glycogen, accounting for about 60 ~ 70%. 50 In the state of insulin resistance, the activation effect of insulin on PPP1CC is weakened, thus reducing the activity of GYS1, resulting in decreased glycogen synthesis and increased blood glucose in T2D patients. 51 Our investigation further corroborated that GYS1 and PPP1CC were target genes of miR-140-5p and had effects on the glycose consumption and glycose uptake, which provided a novel mechanism through which miR-140-5p could regulate the insulin resistance in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“… 48 , 49 During the transport of glucose into cells, glycogen synthesis, oxidative decomposition and other metabolic processes, protein phosphatase 1 (PP1) pathway is the most important metabolic process for synthesizing glucose into glycogen, accounting for about 60 ~ 70%. 50 In the state of insulin resistance, the activation effect of insulin on PPP1CC is weakened, thus reducing the activity of GYS1, resulting in decreased glycogen synthesis and increased blood glucose in T2D patients. 51 Our investigation further corroborated that GYS1 and PPP1CC were target genes of miR-140-5p and had effects on the glycose consumption and glycose uptake, which provided a novel mechanism through which miR-140-5p could regulate the insulin resistance in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies that examined the traffic of full-length PC1 showed that the VxP motif is dispensable for ciliary delivery, that full-length PC1 targeting to cilia is not perturbed by ARF4 depletion, and that endogenous PC1 does not bind ARF4 in collecting duct cells (88,89,149,165). Such differences might be due to the requirement for PC2 in traffic of full-length PC1 but not the chimeric PC1 protein (109,149).…”
Section: Arf4mentioning
confidence: 99%
“…Protein phosphatase one interacts with AKAP220 primarily through its KVQF motif ( Schillace and Scott, 1999 ) and has recently been implicated in trafficking of polycystin-1 to cilia ( Luo et al, 2019 ). We used CRISPR-Cas9 gene editing to generate a knock-in cell line where the phosphatase-targeting motif was replaced by a TATA sequence ( Figure 3A & B ; Figure 3—figure supplement 1A & B ).…”
Section: Resultsmentioning
confidence: 99%